(untitled) (Foro de Educacion, 2018)
This article discusses the educational policies of international organizations, especially those concerning global citizenship and their implications for cyberculture/cyberspace as well as the possibility of implementing a counter-education project, as envisaged by Ilan Gur Ze’ev, the important Israeli philosopher of education, who died in 2012. In connection to this, we ask the question: what kind of individuals should we be in the digital world? To answer this question, we engaged with the UNESCO proposal of Education for Global Citizenship, which seeks to promote a wholistic, educated, engaged and moral attitude amongst the young worldwide, and how this influences cyberculture as a postmodern condition. Gur Ze’ev’s approach would be critical of any attempt at presenting a utopian ideal; most importantly, counter-education notes that once an ideal is set as the objective, then meaningful educational development has become constrained. Thus, we see in utilizing his counter-education the possibility of a thorough, meaningful and critical reflection on issues surrounding cyber-culture as affected by the approach of Education for Global Citizenship. We conclude that it is possible to develop counter-education within the movement for global citizenship, being properly founded on a critical approach to what is being proposed by international organizations as desirable learning objectives.